2015
DOI: 10.1017/s0022215115000481
|View full text |Cite
|
Sign up to set email alerts
|

How many Epley manoeuvres are required to treat benign paroxysmal positional vertigo?

Abstract: Symptomatic control of benign paroxysmal positional vertigo was obtained following a single Epley manoeuvre for 47 per cent of patients. The majority of patients (84 per cent) experienced symptomatic improvement following three Epley manoeuvres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…Some patients learn to treat themselves. A single Epley maneuver has a success rate of up to 80 % [13, 14]; the success rate increases to over 90 % with four repetitions on the same day. Previous head trauma and prolonged bedrest are risk factors for a poor outcome after a single Epley maneuver, while BPV secondary to some inner ear disease is not [15].…”
Section: Posterior Canal Bpvmentioning
confidence: 99%
“…Some patients learn to treat themselves. A single Epley maneuver has a success rate of up to 80 % [13, 14]; the success rate increases to over 90 % with four repetitions on the same day. Previous head trauma and prolonged bedrest are risk factors for a poor outcome after a single Epley maneuver, while BPV secondary to some inner ear disease is not [15].…”
Section: Posterior Canal Bpvmentioning
confidence: 99%
“…Our study yielded similar results since the response rates of 75.32 and 92.20% after 1 day and 1 week follow up were observed, which could be explained by the number of maneuvers. Some studies showed that the canalith repositioning maneuver in treating PC-BPPV should be repeatedly applied ( 5 , 10 ). Thus, patients with PC-BPPV needed to be treated several times, which is inconvenient.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of PC-BPPV relies on a canalith repositioning maneuver, and the most common approach is the Epley maneuver ( 4 ). In a retrospective study, 84% of patients obtained symptomatic control of PC-BPPV after three Epley maneuvers ( 5 ), which means repeated Epley maneuvers are required for some patients until PC-BPPV resolves completely. PC-BPPV also has a high recurrence rate ( 6 , 7 ) and frequent recurrences render patients with PC-BPPV dependent on costly and time-consuming medical care.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if the manoeuver is not effective we recommend a more complete evaluation, using exams such as the caloric test and the video head impulse test (vHIT). Alternatively, any posturography protocol can be used as a complementary exam in order to provide a prognosis [15].…”
Section: Discussionmentioning
confidence: 99%